1991
DOI: 10.1126/science.1749936
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic and Ligand-Independent Activation of Steroid Hormone Receptors

Abstract: The current view of how steroid hormone receptors affect gene transcription is that these receptors, on binding ligand, change to a state in which they can interact with chromatin and regulate transcription of target genes. Receptor activation is believed to be dependent only on this ligand-binding event. Selected steroid hormone receptors can be activated in a ligand-independent manner by a membrane receptor agonist, the neurotransmitter dopamine. In vitro, dopamine faithfully mimicked the effect of progester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
253
0
5

Year Published

1993
1993
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 561 publications
(270 citation statements)
references
References 48 publications
12
253
0
5
Order By: Relevance
“…Despite attempts to do so, this phenomenon has not been reliably demonstrated for human PRs (38). In addition to chicken PRs, several other nuclear receptors can be activated by dopamine through D1 receptors (39), and dopamine placed directly into the third ventricle of the brain increases female rat sexual behavior in a progesterone-independent, but PR-dependent manner (40). Interestingly, two genes regulated by PR-A in a ligand-independent manner, ENC1 and the cell adhesion molecule DSCAM (data not shown), are expressed at high levels in neuronal cells and may be additional brain targets of unliganded PRs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite attempts to do so, this phenomenon has not been reliably demonstrated for human PRs (38). In addition to chicken PRs, several other nuclear receptors can be activated by dopamine through D1 receptors (39), and dopamine placed directly into the third ventricle of the brain increases female rat sexual behavior in a progesterone-independent, but PR-dependent manner (40). Interestingly, two genes regulated by PR-A in a ligand-independent manner, ENC1 and the cell adhesion molecule DSCAM (data not shown), are expressed at high levels in neuronal cells and may be additional brain targets of unliganded PRs.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we have shown that in prostatic adenocarcinomas with focal neuroendocrine differentiation, most of the surrounding non-neuroendocrine tumour cells display nuclear AR expression, independently of the previous therapeutic regimen. Power et al (1991) demonstrated that a catecholamine neurotransmitter could induce ligand-independent activation of some steroid receptors (progesterone receptor and oestrogen receptor) via a cell membrane associated dopamine receptor. If a similar ligand independent activation mechanism also applies to AR, biogenic amines derived from neuroendocrine cells could similarly play a major role in the process of androgen independent activation of (AR positive) tumour ceils.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have documented e ects upon gene activation by nuclear receptors via epidermal growth factor (EGF) (Kato et al, 1995;Bunone et al, 1996;Ignar-Trowbridge et al, 1993), dopamine (Power et al, 1991;Smith et al, 1993), TGFa, (IgnarTrowbridge et al, 1993), insulin-like-growth factor I (IGF-I) (Aronica and Katzenellenbogen, 1993;, cAMP (Aronica and Katzenellenbogen, 1993;Denner et al, 1990), and heregulin (Pietras et al, 1995). Data from several laboratories suggest that this second pathway of NHR activation may result in either ligand-independent receptor activation (Bunone et al, 1996;Ignar-Trowbridge et al, 1993) or augmentation of ligand-dependent receptor signaling (Aronica and Katzenellenbogen, 1993;Kato et al, 1995;Ingar-Trowbridge et al, 1993).…”
Section: Introductionmentioning
confidence: 99%